Gender perspective in flood risk management: a case study in Dodhara-Chandani areas of Kanchanpur district, far western Nepal (Journal of Nepal Geological Society, 2016)
Nepal is among the most vulnerable countries regarding climate-induced-disasters. Nepal is ranked 30th among 198 countries in flood hazard. Climate change associated vulnerability is contextual and gender specific as it impacts men and women differently. It intensifies the socially created inequalities between men and women where women are always the worst victim for their gender differentiated roles and lack of access and control over resources.This paper discusses gender perspective on climate induced disaster, its impact and adaptation in Dodhara and Chandani VDCs of the Kanchanpur district based on the both primary and secondary sources of data. The primary information was collected using structured questionnaire from 96 households, key informant interviews and focus group discussion in both VDCs. The meteorological data (30 years) particularly rainfall and temperature were analysed to see the rainfall pattern and temperature trends. Analysis of temperature data revealed increment of mean annual temperature by 0.02° C per year, which verified the increase in number of warmer days in the study area. The analysis of rainfall data confirmed that the rainfall trend was declining by 1.66 mm per year in monsoon. The average monsoon rainfall recorded in the Mahendranagar Station was 413.4 mm (1984- 2013). However, people recently experience heavy rainfall in monsoon. Women were found dependent on men during disaster period. Although people were not practicing any scientific adaptive measures, a few people have knowledge regarding the disaster preparedness in both VDCs. Environmental impacts after flood period was also observed.